China, Europe, and the Great Divergence: Further Concerns about the Historical GDP Estimates for China - Peter M. Solar (European Historical Economics Society (EHES), 2021)
Broadberry, Guan and Li (2018) made estimates for China's GDP per capita from 980 to 1840 in order to date the onset of the Great Divergence between China and western European economies. In response to Solar's (2021) criticisms, they (2021) made some revisions to the estimates but largely dismissed most of Solar's concerns, particularly those about their series for China's population and its implications for dating the Great Divergence. This working paper assesses their revisions, reaffirms concerns about the level of their 1840 benchmark, and points out the weaknesses of the population figures in greater detail. The dating of the Great Divergence turns out to depend on the population series used and on the interpretation of what was happening to incomes in China during the mid-seventeenth century. This paper recommends considerable skepticism about Broadberry, Guan and Li's estimates.
Keywords: E1; N15; O47; O53; 330; China; Great Divergence; historical national accounts; population